Improving students’ writing skill by using cooperative learning (think, pair, share) technique at grade VIII-7 SMP Negeri 1 Padangsidimpuan - Disran Disran; M. Zaim; Yenni Rozimela (International Conferences on Educational, Social Sciences and Technology)
This research was conducted to improve the students’writing skill at grade VIII-7 SMP Negeri 1 Padangsidimpuan.. It was due to the lack of the students’ interest and less of communication or sharing ideas in writing activity, so they were not able to complete their writing tasks by organizing their ideas, use correct grammar, and choose vocabulary during learning and teaching process. This research was intended to improve the students’ writing skill by using cooperative learning (think, pair, share) technique at grade VIII-7 SMP Negeri 1 Padangsidimpuan. It was hoped that by using this technique the students’ writing skill of grade VIII-7 SMP Negeri 1 Padangsidimpuan could be improved. The participants of this research were the students of grade VIII-7 SMP Negeri 1 Padangsidimpuan in 2012 – 2013 acdemic year. After finishing the first and second cycle of the research, there was some improvement in writing test scores.